Reimplante de pulgar: caso clínico - Sepúlveda, Sergio; Infante, Carlos; Valenzuela, Germán; Compan, Alvaro; Seguel, Jorge (Revista Hospital Clínico Universidad de Chile, 1997)
We report a successful case of a complete thumb amputation. The conditions of the wound surfaces were pretty sharp and contamination was slight. The replantation surgery was done by the same team.After a two months follow up the restoration of thumb function was satisfactory.